Rational design, synthesis, evaluation and enzyme–substrate structures of improved fluorogenic substrates for family 6 glycoside hydrolases. (7th December 2012) - Wu, Miao; Nerinckx, Wim; Piens, Kathleen; Ishida, Takuya; Hansson, Henrik; Sandgren, Mats; Ståhlberg, Jerry
<x xml:space="preserve">Abstract</x> Methylumbelliferyl‐β–cellobioside (MUF–G2) is a convenient fluorogenic substrate for certain β–glycoside hydrolases (GH). However, hydrolysis of the aglycone is poor with GH family 6 enzymes (GH6), despite strong binding. Prediction of the orientation of the aglycone of MUF–G2 in the +1 subsite of Hypocrea jecorina Cel6A by automated docking suggested umbelliferyl modifications at C4 and C6 for improved recognition. Four modified umbelliferyl‐β–cellobiosides [6–chloro‐4–methyl‐ (ClMUF); 6–chloro‐4‐trifluoromethyl‐ (ClF3MUF); 4–phenyl‐ (PhUF); 6–chloro‐4–phenyl‐ (ClPhUF)] were synthesized and tested with GH6, GH7, GH9, GH5 and GH45 cellulases. Indeed the rate of aglycone release by H. jecorina Cel6A was 10–150 times higher than with MUF–G2, although it was still three orders of magnitude lower than with H. jecorina Cel7B. The 4–phenyl substitution drastically reduced the fluorescence intensity of the free aglycone, while ClMUF–G2 could be used for determination of kcat and KM for H. jecorina Cel6A and Thermobifida fusca Cel6A. Crystal structures of H. jecorina Cel6A D221A mutant soaked with the MUF‐, ClMUF‐ and ClPhUF‐β–cellobioside substrates show that the modifications turned the umbelliferyl group 'upside down', with the glycosidic bond better positioned for protonation than with MUF–G2. Database Structural data have been submitted to the Protein Data Bank under accession numbers pdb 4AU0, 4AX7, 4AX6 Structured digital abstract http://mint.bio.uniroma2.it/mint/search/interaction.do?interactionAc=MINT-7260296 Cel6A and Cel6A bind by x-ray crystallography (View Interaction: 1, 2)